Energy reuse of sewage treatment plant sludge - Moura, Ana Flávia Fagundes (2020)
This work aimed to evaluate the capacity of the energy reuse of sludge from an urban sewage treatment plant (ETE), in order to determine the technical and economic viability of this final sludge destination, in comparison with the final disposal in landfill. The bibliographic analysis carried out shows that from an energetic point of view, the sludge from an urban sewage treatment plant, digested anaerobically, has a high organic load and a high calorific value in relation to other combustible biomasses. Therefore, its reuse can be economically and environmentally advantageous. The disposal of sludge in landfills, despite its simplicity, presents environmental problems, such as the possibility of contamination of groundwater, soil and emission of pollutants. The investigation shows that in the energy reuse, the processes of conversion of sludge into energy such as pyrolysis and incineration, presented satisfactory results, however they are processes of high cost of operation and maintenance.